Comparison of apportionment methods for assigning trip data to rezoned traffic analysis zones: A case study of Toronto, Canada. (1st February 2021) - Yao, Hong; Chen, DongMei
Abstract : Due to regional development impacts, existing traffic analysis zones may be rezoned. Apportioning data to new traffic analysis zones is essential to ensure data analysis consistency and comparability. The traditional method uses area to apportion data. This study introduces six methods in apportioning trip data, including the traditional method (M1); the residential land use counted method (M2); the population counted at the dissemination area (DA) level method (M3); the integrated method using both residential land use and the population in DAs (M4); the population counted at the dissemination block (DB) level method (M5); and the integrated method using both residential land use and the population in DBs (M6). These methods are demonstrated in the case of Toronto, Canada using trip data from 2001 and 2016. Results from the six methods are compared and analyzed using mapping, Getis‐Ord Gi* hot‐spot analysis, and the Wilcoxon signed‐rank test. Our findings show that the traditional method and the population counted in DAs method are significantly different (p < 0.05) from the residential land use counted method and the integrated method using both residential land use and the population in DAs and the integrated method using both residential land use and the population in DBs. These results provide references for selecting appropriate apportionment methods, which is the basis for transportation planning and policymaking. Key Messages: Six apportionment methods for assigning trip data to rezoned traffic analysis zones were examined using the trip data of Toronto from 2001 and 2016. The apportionment results from the six methods were compared using hot‐spot analysis and the Wilcoxon signed‐rank test. The results of comparisons provide references for the choices of methods in apportioning trip data. Comparaison des méthodes de répartition des données liées aux déplacements au sein des zones d'analyse du trafic : une étude de cas de la région de Toronto, Canada: Considérant le développement urbain à l'échelle régionale, les zones d'analyse du trafic devraient être reconfigurées dans la région de Toronto. Pour ce faire, il est essentiel d'associer les données aux nouvelles zones d'analyse du trafic afin d'assurer la cohérence et la comparabilité des données. La méthode traditionnelle utilise la zone pour répartir ou attribuer les données. La présente étude compare six méthodes d'attribution des données liées aux déplacements, c'est‐à‐dire la méthode traditionnelle (M1), la méthode de dénombrement de l'usage des terrains résidentiels (M2), la méthode fondée sur le niveau du dénombrement de la population dans l'aire de diffusion (AD) (M3), la méthode intégrée utilisant l'usage des terrains résidentiels et la population dans les AD (M4), la méthode fondée sur le niveau du dénombrement de la population dans l'îlot de diffusion (ID) (M5) et, finalement, la méthode intégrée utilisant l'usage des terrains résidentiels et la population dans les ID (M6). Ces diverses méthodes sont expérimentées dans la région de Toronto, au Canada, en utilisant les données liées aux déplacements de 2001 à 2016. Les résultats des traitements des six méthodes sont comparés et analysés en utilisant la cartographie, l'analyse des points chauds Getis‐Ord Gi* et le test Wilcoxon signed‐rank. Nos conclusions montrent que la méthode traditionnelle et le dénombrement de la population dans la méthode des AD sont sensiblement différents des autres méthodes. Ces résultats fournissent des informations sur le choix des méthodes appropriées de répartition des données sur le trafic, ce qui constitue un élément important pour l'élaboration de politiques et la planification en matière de transport.